Genital tuberculosis in postmenopausal women with variable clinical presentations: A report of 3 cases - Ashima Arora; Shameema Anvar Sadath (Elsevier, 2018)
Genital tuberculosis is usually diagnosed in young women being assessed for infertility. After menopause it usually presents with symptoms resembling endometrial malignancy, such as postmenopausal bleeding, persistent vaginal discharge and pyometra. The diagnosis is made by detection of acid-fast bacilli on microscopy or bacteriological culture and/or presence of epithelioid granuloma on biopsy. Anti-tubercular therapy involves the use of rifampicin, isoniazid, pyrazinamide and ethambutol. Surgery is indicated if a pelvic mass and recurrence of pain or bleeding persist after 9 months of treatment. Three cases of genital tuberculosis in postmenopausal women with different clinical presentations are reported. The first woman presented with ascites and weight loss. The second had postmenopausal bleeding with a pipelle biopsy suggestive of endometrial intraepithelial neoplasia. The third presented with weight loss and a palpable abdominal mass. Pelvic malignancy was initially suspected but a diagnosis of tuberculosis was made following pre-operative endometrial biopsy, bacteriological culture and intra-operative frozen section. All three women responded to anti-tubercular therapy. Keywords: Genital tuberculosis, Postmenopausal, Endometrial intraepithelial neoplasia, Anti-tubercular therapy, Endometrial biopsy